Intradermal Tests With Drugs: An Approach to Standardization - Barbaud, Annick; Weinborn, Marie; Garvey, Lene Heise; Testi, Sergio; Kvedariene, Violeta; Bavbek, Sevim; Mosbech, Holger; Gomes, Eva; Aberer, Werner; Elberink, Hanneke N. G. Oude; Torres, Maria Jose; Ponvert, Claude; et al. (Frontiers in Medicine, 2020)
Background: Intradermal tests (IDTs) are performed and interpreted differently in drug allergy centers making valid comparison of results difficult. Objective: To reduce method-related and inter-center variability of IDTs by the introduction of a standardized method. Materials and methods: In 11 centers of the European Network for Drug Allergy, IDTs were prospectively performed with saline and with amoxicillin (20mg/ml) using (1) the local method and (2) the standardized ENDA method (0.02ml). The diameters of the initial injection wheal (Wi) for the different volumes and sites injected obtained from each center were analyzed. Results: The most reproducible method was to fill a syringe with test solution, then expel the excess fluid to obtain exactly 0.02 ml. The median Wi diameter with 0.02 ml injection using the standardized method was 5 mm (range 2-10 mm; interquartile range (IQR) 5-5 mm; n=1096) for saline and 5 mm (range 2-9 mm; IQR= 4.5-5 mm; n=240) for amoxicillin. IDT injection sites did not affect the Wi diameter. Training improved precision and reduced variability of Wi diameters. Conclusion: Using the standardized IDT method described in this multi-center study helped to reduce variability, enabling more reliable comparison of results between individuals and centers.